2022
DOI: 10.1136/bmjgast-2022-000871
|View full text |Cite
|
Sign up to set email alerts
|

Lost microbes of COVID-19:Bifidobacterium,Faecalibacteriumdepletion and decreased microbiome diversity associated with SARS-CoV-2 infection severity

Abstract: ObjectiveThe study objective was to compare gut microbiome diversity and composition in SARS-CoV-2 PCR-positive patients whose symptoms ranged from asymptomatic to severe versus PCR-negative exposed controls.DesignUsing a cross-sectional design, we performed shotgun next-generation sequencing on stool samples to evaluate gut microbiome composition and diversity in both patients with SARS-CoV-2 PCR-confirmed infections, which had presented to Ventura Clinical Trials for care from March 2020 through October 2021… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 41 publications
(55 reference statements)
7
65
4
1
Order By: Relevance
“…belong to the same phylum as a critically important constituent of the gut microbiome and common ingredient of probiotics, Bifidobacterium . Bifidobacterium abundance is known to decrease in SARS-CoV-2-infected subjects, as seen in ours and other studies ( Tao et al, 2020 ; Xu et al, 2020 ; Reinold et al, 2021 ; Yeoh et al, 2021 ; Zuo et al, 2021 ; Hazan et al, 2022b ). We have anecdotally observed, through our clinical experiences pre and post Fecal Microbiota Transplant, that certain bacteria in the same phylum may be able to replace each other’s function.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…belong to the same phylum as a critically important constituent of the gut microbiome and common ingredient of probiotics, Bifidobacterium . Bifidobacterium abundance is known to decrease in SARS-CoV-2-infected subjects, as seen in ours and other studies ( Tao et al, 2020 ; Xu et al, 2020 ; Reinold et al, 2021 ; Yeoh et al, 2021 ; Zuo et al, 2021 ; Hazan et al, 2022b ). We have anecdotally observed, through our clinical experiences pre and post Fecal Microbiota Transplant, that certain bacteria in the same phylum may be able to replace each other’s function.…”
Section: Introductionsupporting
confidence: 88%
“…Ours and other data also support a protective role of Bifidobacterium in SARS-CoV-2 infection, possibly through these immune functions of Bifidobacterium . Our study and others ( Tao et al, 2020 ; Xu et al, 2020 ; Reinold et al, 2021 ; Yeoh et al, 2021 ; Zuo et al, 2021 ; Hazan et al, 2022b ) show that the gut microbiome, particularly Bifidobacterium levels, relates to positivity and severity of SARS-CoV-2 infection. Tao et al (2020) showed that changes in gut microbiota composition might contribute to SARS-CoV-2-induced production of inflammatory cytokines in the intestine, which may lead to the cytokine storm onset.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Patients with severe SARS-CoV-2 infection had significantly lower bacterial diversity, and lower relative abundances of Bifidobacterium, Faecalibacterium, and Roseobacter in the gut microbiome, as well as increased Bacteroides spp. [87]. Thus, during the SARS-CoV-2 pandemic, gut microbiota correction may help to improve population immunity and protect public health [88].…”
Section: Sars-cov-2 and Gut Microbiomementioning
confidence: 99%